The importance of the clinical record in the implantdontics planning: Clinical, ethical and legal aspects (Research, Society and Development, 2022)
The process for installing a dental implant must be carried out with the precision of planning that includes a complete medical record with all the information about the patient and the implant that will be performed. Many factors must be considered for the perfect execution of one or more dental implants, in order to safeguard both patient and professional. The objective of the present study was to clarify the importance of good planning, which deepens the knowledge of the patient's particularities, seeking to verify the relationship between implant failures and errors in the collection of data prior to surgery, also addressing topics of a dental record, and the legal parameters for the digitization and storage time of these records. Adequate planning composition, dental records and documentation need to be highlighted in the literature, since they are topics that, when becoming clinical routine, can make the difference between success and failure in Implantology. In the reviewed works, the importance of having a clear exposure of the treatment to the patient with all the information about the entire process stands out, in order to guarantee compliance with the Consumer Protection Code and the Dental Ethics Code, leading to the existence of a consent form so that both parties have legal protection and confidence in the treatment.